Dean Acheson and Fletcher Dean Robert Stewart with a group of students - Unknown (Tufts Archival Research Center, 2008)
8x10. Standing from left to right: Samuel F. Hart, Owen M. Quattlebaum, Julien J. Hohenberg, Thomas W. Bosnor; seated: Dean Acheson, Rebecca K. Glass, Robert Stewart.